(untitled) (Proceedings of the International Conference on Public Health, 2017)
Globally, HIV epidemic has entered a critical condition. A number of HIV cases for each Province in Indonesia’s that second-highest in the province of East Java with a number of cases were began 1987 – March 2016 in East Java were 26,052 people. A number of HIV women patients until March 2016 was 74,512 people. The clinic VCT data until 30 November 2015 a number of 657 patients receiving ARV. 49 people have died, 10 people referred to and 20 people drop out. Routine control on schedule and regularly drank to ARV was 273 people and irregular drank to ARV was 297 people. The aim to analysis the relationship of self concept with medication adherence to ARV in HIV-positive women’s reproductive in Poly VCT Waluyojati General Hospital Probolinggo Indonesia. The methods use analytic correlational with cross sectional study. The study population all HIV-positive women on reproductive who visit and get treatment medication to ARV in Clinic VCT Waluyojati General Hospitals were 81 people and a sample were 68 people using consecutive sampling. After asking informed concent to respondent, data collection with questionnaire and statistical tests pearson product moment. The results showed a P value = 0.167 < 0.05. Conclusion that there were no relationship of self concept with adherence to ARV medication of HIV-positive women on reproductive age. We give recommendation on next study that you must conduct to control confounding variable and partisipatory observations to search for the real cause of someone not adherence to ARV medication.